2011
DOI: 10.1007/s12161-011-9314-1
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Antioxidant Capacity of Unprocessed and Processed Food Products by Spectrophotometric Methods

Abstract: Two electron transfer (ET) reaction-based methods, ferric reducing antioxidant power (FRAP) and Folin-Ciocalteu (FC) reducing capacity, were used for the determination of total antioxidant capacity of vegetable oils (rapeseed, palm and extra virgin olive oils), meat samples (poultry and pork) and potatoes before and after the frying process under domestic frying conditions. Before frying, potatoes had the highest FRAP value (276.7 μmol Trolox/100 g), whereas extra virgin olive oil revealed the highest FolinC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
(56 reference statements)
4
11
0
Order By: Relevance
“…A positive and linear correlation (r = 0.90; p < 0.05) between the two methodologies used for the antioxidant activity evaluation for all limpets pâté samples was found. This correlation is in line with those reported by Szydłowska-Czerniak et al [49], which proved the benefit of the Folin-Ciocalteu reducing capacity method for the assessment of the total antioxidant capacity of food samples.…”
Section: Evaluation Of Antioxidant Capacity and Oxidative Stability Osupporting
confidence: 92%
See 2 more Smart Citations
“…A positive and linear correlation (r = 0.90; p < 0.05) between the two methodologies used for the antioxidant activity evaluation for all limpets pâté samples was found. This correlation is in line with those reported by Szydłowska-Czerniak et al [49], which proved the benefit of the Folin-Ciocalteu reducing capacity method for the assessment of the total antioxidant capacity of food samples.…”
Section: Evaluation Of Antioxidant Capacity and Oxidative Stability Osupporting
confidence: 92%
“…A positive and linear correlation (r = 0.90; p < 0.05) between the two methodologies used for the antioxidant activity evaluation for all limpets pâté samples was found. This correlation is in line with those reported by Szydłowska-Czerniak et al [49], which proved the benefit of the Folin-Ciocalteu reducing capacity method for the assessment of the total antioxidant capacity of food samples. Lipid oxidation is one of the major problems concerning food quality deterioration, mainly in fish products due to the higher proportions of long chain unsaturated fatty acids making them more susceptible to oxidation [37].…”
Section: Evaluation Of Antioxidant Capacity and Oxidative Stability Osupporting
confidence: 92%
See 1 more Smart Citation
“…Nowadays, the most widely used methods for measuring TAC are those that involve the generation of radical species and the presence of antioxidants determining the scavenging of these radicals (Szydlowska-Czerniak et al 2012). Nevertheless, oxygen radical absorbance capacity (ORAC) and trolox equivalent antioxidant capacity (TEAC) assays are the most commonly used hydrogen atom transfer and electron transfer methods, respectively (Huang et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, many studies have demonstrated the high relevance of the total antioxidant capacity (TAC) of phenolic compounds to their remarkable health-promoting benets. [1][2][3] Therefore, the determination of the TAC of polyphenolic compound-rich or enriched foods, nutraceuticals and other dietary supplements has become fundamental in the food industry. 5 Several in vitro chemical-based methods, with different advantages and disadvantages, have been critically evaluated and extensively applied including 1,1-diphenyl-2picrylhydrazyl (DPPH) and 2,2-azino-bis-(3ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS) radical scavenging assays and ferric reducing antioxidant power (FRAP) assay.…”
Section: Introductionmentioning
confidence: 99%